2019
DOI: 10.1111/ajt.15307
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of changes to lung allocation policy

Abstract: Organ allocation for transplantation aims to balance the principles of justice and medical utility to optimally utilize a scarce resource. To address practical considerations, the United States is divided into 58 donor service areas (DSA), each constituting the first unit of allocation. In November 2017, in response to a lawsuit in New York, an emergency action change to lung allocation policy replaced the DSA level of allocation for donor lungs with a 250 nautical mile circle around the donor hospital. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 9 publications
4
49
0
Order By: Relevance
“…The rationale for prioritizing patients based on proximity re ects both system e ciency and organ viability considerations, as transporting lungs over long distances incurs transportation costs, travel time by the surgical recovery team, and potentially detrimental effects of organ ischemia time [15][16][17][18][19]. The manner and degree to which proximity should in uence candidate rankings is a matter of ongoing debate [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for prioritizing patients based on proximity re ects both system e ciency and organ viability considerations, as transporting lungs over long distances incurs transportation costs, travel time by the surgical recovery team, and potentially detrimental effects of organ ischemia time [15][16][17][18][19]. The manner and degree to which proximity should in uence candidate rankings is a matter of ongoing debate [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…An emergency change to lung allocation policy was instituted after a court challenge in 2017, changing allocation from one based on donor service areas to one that would offer organs within a 200-nautical-mile radius of the transplant center (crossing over donor service areas). An analysis by Puri et al 13 revealed that after this change, there was no difference in 30-, 60-, or 90-day mortality of patients at their center (so no overall improvement in utility), but the organ retrieval costs increased significantly, from $34 000 to $70 000 per organ. Additionally, there was a significant increase in the mean ischemic time, from 204 to 244 minutes, meaning that the organs spent more time "on ice" instead of in the body of the recipient, which could adversely affect long-term survival.…”
Section: Sarah Murnaghan: Challenging the Evidence On Allocationmentioning
confidence: 99%
“…Additionally, there was a significant increase in the mean ischemic time, from 204 to 244 minutes, meaning that the organs spent more time "on ice" instead of in the body of the recipient, which could adversely affect long-term survival. 13 The authors of this study stated as follows:…”
Section: Sarah Murnaghan: Challenging the Evidence On Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…New organ allocation policies that mandate broader sharing highlight the need to urgently address transportation safety. Implementation of the new thoracic organ allocation system has already led to a 45% increase in the median distance for lung recovery 7,8 . The recently implemented liver reallocation policy is predicted reduce local allocation from 76% to approximately 10%, increased air travel from 50% to 71% of recoveries 9,10 .…”
Section: Introductionmentioning
confidence: 99%